Bioavailable trace metals and their ecological risks in the tourist beaches of the Southeast coast of India. (November 2020) - Krishnakumar, S.; Vidyasakar, A.; Anbalagan, S.; Godson, Prince S.; Kasilingam, K.; Parthasarathy, P.; Pradhap, D.; Saravanan, P.; Hariharan, S.; Rajkumar, A.; Neelavannan, K.; Magesh, N.S.
Abstract: The concentration of Acid Leachable Trace Metals (ALTMs) was assessed in urbanized tourist beaches (96 samples from Marina beach, 34 samples from Edward Elliot's beach, and 28 samples from Silver beach) of southeast coast of India. The concentration of metals accumulated in the beach sediment was less than the Upper Continental Crust (UCC) background reference values. The mean enrichment of ALTMs in the studied urban tourist beaches showed the following descending order: Marina beach – Cr > Pb > Ni > Zn > Cu > Mn > Co; Edward Elliot's beach – Cr > Pb > Ni > Mn > Co > Zn > Cu; Silver beach – Cr > Pb > Ni > Co > Mn > Cu > Zn. The ALTMs such as Fe, Mn, Co, Cu, and Zn were probably derived from natural weathering and mild anthropogenic influences whereas other metals were derived from anthropogenic induced factors. Highlights: Concentration of metals in sediment was assessed from the urban beaches of India. The concentration of metals was less than the UCC background reference values. The source of metals was derived from anthropogenic impact and riverine process.